Discrete mathematics and structures - Gupta, Satinder Bal (Laxmi Publications, 2006)
Discrete mathematics and structures / Gupta, Satinder Bal. -- Kolkata: Laxmi Publications, 2006 511.3 G978e3 3rd ed. No. of Copies : 1